2023
DOI: 10.1038/s41598-023-32439-1
|View full text |Cite
|
Sign up to set email alerts
|

Laser cooling with intermediate state of spin–orbit coupling of LuF molecule

Abstract: This work presents a theoretical study of the laser cooling feasibility of the molecule LuF, in the fine structure level of approximation. An ab-initio complete active space self-consistent field (CASSCF)/MRCI with Davidson correction calculation has been done in the Λ(±) and Ω(±) representations. The corresponding adiabatic potential energy curves and spectroscopic parameters have been investigated for the low-lying electronic states. The calculated values of the internuclear distances of the X3Σ0+ and (1)3Π0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Osika et al [25] reported that the effective cooling scheme for the RaF molecule can be realized using only one pump laser. Very recently, El-Kork et al [26] reported a three-laser cooling scheme including intervening electronic states for LuF. Bigagli et al [27] built a cycling scheme for Doppler cooling of trapped OH + ions using X 3 Σ − ↔ A 3 Π transition.…”
Section: Introductionmentioning
confidence: 99%
“…Osika et al [25] reported that the effective cooling scheme for the RaF molecule can be realized using only one pump laser. Very recently, El-Kork et al [26] reported a three-laser cooling scheme including intervening electronic states for LuF. Bigagli et al [27] built a cycling scheme for Doppler cooling of trapped OH + ions using X 3 Σ − ↔ A 3 Π transition.…”
Section: Introductionmentioning
confidence: 99%